2010
DOI: 10.1111/j.1545-5300.2010.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of Psychological Well‐Being in Dementia Caregivers: The Link Between Marital Communication and Depression

Abstract: Dementia research has frequently documented high rates of caregiver depression and distress in spouses providing care for a partner suffering from dementia. However, the role of marital communication in understanding caregiver distress has not been examined sufficiently. Studies with healthy couples demonstrated an association between marital communication and the partners' psychological well-being, depressiveness, respectively (e.g., Heene, Buysee, & Van Oost, 2005). The current study investigates the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 63 publications
4
37
0
8
Order By: Relevance
“…AD is the most common form of dementia . A substantial number (40%) of family caregivers (CG) are spouses (Alzheimer's Association, 2016), and epidemiologists predict that future family CGs are more likely to be spouses due to their longer life expectancy and declining birth rates affecting the availability of adult children . Spouse CGs have reported high burden and stress and require $9.7 billion in stress‐related healthcare …”
Section: Introductionmentioning
confidence: 99%
“…AD is the most common form of dementia . A substantial number (40%) of family caregivers (CG) are spouses (Alzheimer's Association, 2016), and epidemiologists predict that future family CGs are more likely to be spouses due to their longer life expectancy and declining birth rates affecting the availability of adult children . Spouse CGs have reported high burden and stress and require $9.7 billion in stress‐related healthcare …”
Section: Introductionmentioning
confidence: 99%
“…The association between marital quality and psychological distress was broadly examined in different samples of Western societies. Happy marital relationship was found to contribute to better psychological health (Barnett et al 1994; Kiecolt-Glaser & Newton 2001; Bloch et al 2010; Braun et al 2010). Also, the marital happiness trajectory was associated with subsequent changes in both life happiness and depressive symptoms (Kamp Dush et al 2008; Waite et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that FCs' negative thoughts and feelings of burden could cause them to focus on their relatives' weaknesses, creating a vicious cycle in the family, during which the FCs' negative orientation lead to negative responses and actions from the PMD, exacerbating tension. Previous research has shown that good quality of daily relationships and positive reciprocal communication can promote FCs' wellbeing [31,45,46] and support the positive adjustment of PMDs. It has also been found that enhanced relationship quality can maintain better emotional wellbeing of both the PMD and the FC, which can lead to more positive experiences of living with a memory disorder [9] .…”
Section: Discussionmentioning
confidence: 99%